Decolonizing Indonesian History Curriculum, 1946-1964 - Utami, Indah Wahyu Puji; Sapto, Ari; Leksana, Grace Tjandra; Ayundasari, Lutfiah (Paramita: Historical Studies Journal, 2024)
Decolonization of history education mainly seeks to decenter Eurocentric narrative in history curriculum and teaching. Whilst this topic has been widely explored, the discussion related to the decolonization of history education has yet to be explored. This research aims to trace the complex process of decolonization of the history curriculum in Indonesia, which took place at the beginning of its independence, and how the political situation might have influenced this process. Historical research was conducted. Archival materials were obtained from various institutions both in Indonesia and overseas. The data were analyzed and interpreted using decolonization as a framework. This research found that the Indonesian government has tried to decolonize the history curriculum by foregrounding the role of Indonesians in History. However, the effort was not easy because the references used in teaching were still written using sources from the colonial period. Moreover, this research shows that political changes could affect the history curriculum.Dekolonisasi pendidikan sejarah terutama berupaya untuk menghilangkan narasi Eurosentris dalam kurikulum dan pengajaran sejarah. Meskipun topik ini sudah banyak dieksplorasi, namun pembahasan terkait dekolonisasi pendidikan sejarah masih belum tereksplorasi. Penelitian ini bertujuan untuk menelusuri kompleksnya proses dekolonisasi kurikulum sejarah di Indonesia yang terjadi pada awal kemerdekaannya, dan bagaimana situasi politik mempengaruhi proses tersebut. Penelitian sejarah dilakukan. Bahan arsip diperoleh dari berbagai institusi baik di Indonesia maupun di luar negeri. Data dianalisis dan diinterpretasikan dengan menggunakan kerangka dekolonisasi. Penelitian ini menemukan bahwa pemerintah Indonesia telah mencoba mendekolonisasi kurikulum sejarah dengan mengedepankan peran masyarakat Indonesia dalam Sejarah. Namun upaya tersebut tidak mudah karena referensi yang digunakan dalam pengajaran masih ditulis menggunakan sumber-sumber dari masa kolonial. Selain itu, penelitian ini menunjukkan bahwa perubahan politik dapat mempengaruhi kurikulum sejarah.